KELAYAKAN SEDIAAN PENYEGAR (FACE TONER) PUTIK BUNGA SAFFRON (CROCUS SATIVUS) SEBAGAI KOSMETIK TRADISIONAL PERAWATAN KULIT WAJAH - Adelina Salvi; Prima Minerva (Universitas Negeri Padang, 2022)
Saffron flower pistil (Crocus Sativus) can be used as the main ingredient in making face toners because saffron flower pistils (Crocus Sativus) contain Vitamin C, Zinc and Flavonoids which can be used as an alternative ingredient for facial skin care. This study aims to a) To analyze how the traditional saffron flower pistil (Crocus Sativus) facial toner is made for facial skin care. b) To analyze the appropriateness of the saffron flower pistil (Crocus Sativus) facial toner, it was seen from the content of Vitamin C, Zinc and Flavonoids found in the saffron flower pistil (Crocus Sativus). c) To analyze the appropriateness of the saffron flower pistil (Crocus Sativus) facial toner preparation seen from the aroma, absorption, color and preferences of the panelists. This type of research is experimental. The place to test the content of B-Carotene, Flavonoids, and Lycopene contained in the saffron flower pistil (Crocus Sativus) facial toner was conducted at the FMIPA UNP Laboratory. And the place to do the argonoleptic test was done at the Laboratory of the Cosmetology and Beauty Study Program of UNP. The object of research is the Saffron flower pistil (Crocus Sativus) which is made into a face toner for facial skin care, the ingredients contained in the saffron flower pistil (Crocus Sativus) facial toner for facial skin care, and its organoleptic properties. Face toner preparations include aroma, absorption, color and preferences of panelists (hedonic test. Data sources from observation, documentation, and questionnaires. Panelists as many as 7 people. Descriptive data analysis technique by displaying statistics and frequency. Based on the results of the research, it was found that 1.41% of the saffron flower pistil (Crocus Sativus) face toner was made in this study. Based on the organoleptic test, it showed that the aroma, color and preferences of the panelists had a fairly high level of assessment, while the absorption rate had a low rating because the absorption power of the saffron flower's pistil face toner was not absorbed into the facial skin. It is suggested to the Department of Makeup and Beauty Education, Faculty of Tourism and Hospitality, that the results of this study can be used as input and reference for lecture materials in the cosmetology course that saffron flower pistils (Crocus Sativus) can be used as a face toner as a traditional cosmetic for facial skin care.